2016
DOI: 10.1021/acsami.6b11642
|View full text |Cite
|
Sign up to set email alerts
|

Composite Pillars with a Tunable Interface for Adhesion to Rough Substrates

Abstract: The benefits of synthetic fibrillar dry adhesives for temporary and reversible attachment to hard objects with smooth surfaces have been successfully demonstrated in previous studies. However, surface roughness induces a dramatic reduction in pull-off stresses and necessarily requires revised design concepts. Toward this aim, we introduce cylindrical two-phase single pillars, which are composed of a mechanically stiff stalk and a soft tip layer. Adhesion to smooth and rough substrates is shown to exceed that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 48 publications
5
64
0
Order By: Relevance
“…The design parameters investigated were the thickness of the soft tip layer, the ratio of the elastic moduli, and the curvature of the interface between the two materials ( Figure ). The pull‐off strength values were predicted to increase for thinner layers and larger modulus ratios in accordance with experimental results on model structures (Figure a) . For all elastic modulus ratios, a thinner layer resulted in a decreased magnitude of the edge stress singularity, whereas the stress at the center was increased related to a “confinement” effect .…”
Section: Principles Of Adhesive Micropatternssupporting
confidence: 84%
See 1 more Smart Citation
“…The design parameters investigated were the thickness of the soft tip layer, the ratio of the elastic moduli, and the curvature of the interface between the two materials ( Figure ). The pull‐off strength values were predicted to increase for thinner layers and larger modulus ratios in accordance with experimental results on model structures (Figure a) . For all elastic modulus ratios, a thinner layer resulted in a decreased magnitude of the edge stress singularity, whereas the stress at the center was increased related to a “confinement” effect .…”
Section: Principles Of Adhesive Micropatternssupporting
confidence: 84%
“…Furthermore, the increment of the energy release rate during detachment varied with the extent of confinement. This means that with decreasing film thickness (i.e., larger degree of confinement), the detachment mechanism changes from unstable growth of edge cracks to more stable growth of finger‐like or center cracks . It should be noted that the effect due to confinement of the soft terminal layer depends strongly on material compressibility (i.e., Poisson's ratio) .…”
Section: Principles Of Adhesive Micropatternsmentioning
confidence: 99%
“…Inspired by the unique properties of adhesive surfaces found in nature, micropatterned adhesives are currently under intense research for handling fragile and miniaturized objects, even in demanding environments such as vacuum . Among the various designs, microstructures with mushroom‐shaped tips have an exceptionally high adhesion . It was demonstrated that their pull‐off force, i.e., the force necessary for detaching the adhesive from a substrate, was up to an order of magnitude higher than with nonoptimized flat punch pillars .…”
Section: Introductionmentioning
confidence: 99%
“…Since developing an understanding of the underlying principles of fibrillar adhesive systems in nature, careful attention has been paid to the design and fabrication of synthetic fibrils for both strength and reversibility . Efforts addressing the former have primarily focused on controlling the fibril‐substrate interfacial stress distribution through modification of the tip geometry.…”
Section: Introductionmentioning
confidence: 99%